Factors Affecting Implementation of ISO 9001:2008 Quality Management System in Hospitals: The Case of the Mater Hospital, Nairobi - Moraa, Carol Mitaki (My University, 2011)
The aim of this study was to establish the factors affecting implementation of the ISO 9001:2008 quality management system (QMS) in hospitals, with a focus on The Mater Hospital. To establish the factors, the study aimed at addressing the following objectives: determining the effects of training on implementation of ISO 9001:2008 QMS at The Mater Hospital; assessing the effect of availability of resources on implementation of ISO 9001:2008 QMS at The Mater Hospital, and to establish the extent to which top management support affects implementation of ISO 9001:2008 QMS at The Mater Hospital. The study limited itself to The Mater Hospital, Nairobi, since it was the first hospital in East and Central Africa to be ISO 9001:2000 certified. The study adopted a descriptive design method because it describes the factors affecting implementation of ISO 9001:2008 QMS at The Mater Hospital. The target population for the study was The Mater Hospital staff. 50 employees out of the target population of 500 employees were selected, using stratified random sampling technique, to represent the sample size from the Heads of Departments, Section Managers and non-management staff. The data collection tool used was the questionnaire due to its convenience and cost effectiveness. Finally, the data collected was analyzed using the Statistical Package of Social Sciences (SPSS) version 17.0 and the data presented in tables and graphs. The study found out that all staff should be trained on ISO 9001:2008 QMS, and attend training related to their function in the hospital. Staff should also have regular departmental awareness sessions in ISO 9001:2008 QMS. The effects of training on implementation of ISO 9001:2008 QMS include enhanced knowledge and skills of the people involved in offering services, standardization of healthcare processes and practices at the hospital, and enhanced customer focus. The study also found that availability of resources encourages innovation and creativity in service delivery, and enhances team work, while minimizing individuality. The study findings depict that a hospital’s top management should support the ISO 9001:2008 QMS by organizing awareness sessions, appointing a manager to be in charge of the system, and using the system as a management tool. Further, to support the QMS, the study found that non- conformities should be addressed in consultation with the Heads of Department (HODs), follow up actions should be done by management, the HODs should be responsive to departmental needs, and they should frequently hold departmental meetings on the QMS. The study concluded that training, availability of resources and top management support are factors that affect implementation of the ISO 9001:2008 in hospitals.